Hexachloro benzene in the Nanshan Karst systems, China (Bangladesh Journal of Scientific and Industrial Research, 2015)
Karst areas have much higher ecological vulnerability and are easy to be contaminated with hexachlorinated benzene (HCB) which is introduced as health risk pollutants. HCB concentrations were used to understand the transport of HCB conducted in the Nanshan karst system, China. Water, sediments from the underground river and water, sediments and soil from the surface systems were collected monthly in 2011 - 2012 and HCB were analyzed. The levels of HCB were 19.9 ng L-1 in underground waters and 11.6 ng g-1 in underground sediments while 99.1 ng L-1 in surface waters and 110.5 ng g-1 in surface sediments and 2.8 ng g-1 in soils. Seasonal variations were found in concentrations of HCB both in the waters and the sediments. HCB concentrations varied from 7.8 ng L-1 in winter to 86.9 ng L-1 in spring in the groundwaters and 0.3 ng g-1 in autumn to 36.7 ng g-1 in spring in the underground sediments. HCB concentrations varied from 38.6 ng L-1 in autumn to 1019.8 ng L-1 in spring in the surface waters, 0.7 ng g-1 in autumn to 133.4 ng g-1 in spring in the surface sediments and 2.5 ng g-1 in autumn to 17.4 ng g-1 in winter in soil. The substantial seasonal variation found between underground system and surface system which indicate that the surface systems play major role for the transport and contamination of HCB in the underground river systems due to karst features.Bangladesh J. Sci. Ind. Res. 50(2), 109-116, 2015